DUKUNGAN SUAMI DALAM KEBERHASILAN IBU MEMBERIKAN ASI EKSKLUSIF (USIA 0-6 BULAN) DI DUSUN TALOK MOJOKERTO - Ratnaningsih, Tri (JURNAL KEPERAWATAN SEHAT, 2016)
The success rate of exclusive breastfeeding can be managed successfully with the encouragement of her husband to the mother to breastfeed the baby. Support husbands sometimes do not show up or husband does not seem to care. This is because he does not know the right way to support his wife. The purpose of this research was to determine the mothers husband support in the success of exclusive breastfeeding in Talok Hamlet Salen Village Bangsal Sub District Mojokerto District. This research was descriptive. The population in this research is all mothers with children aged 7-24 months in Talok Hamlet Salen Village Bangsal Sub District MojokertoDistrictas many as 30 people. Sampling technique of this research is total sampling. The variable in this research is the mothers husband support in the success of exclusive breastfeeding. Measuring instrument used was a questionnaire. The results suggest that most of the positive husbands support as many as 17 people (56.1%), and negative ones as many as 13 people (43.9%). Analysis of the data used is mean cut off point. The results of data analysis showed that the husband supports his wife to give breast milk to their babies until the age of 6 months. Husband provide positive support because it is already able to think about the good health of his wife and child so that his wife supports exclusive breastfeeding in mind the importance of exclusive breastfeeding for infants and the many benefits of exclusive breastfeeding.